Pengaruh Modal Kerja terhadap Rentabilitas pada PT. Ades Waters Indonesia Tbk. Jakarta Selama Periode 2002-2009 - Irwan Setiawan (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This study aims to determine how much influence the independent variable Working Capital to Profitability At PT. Ades Waters Indonesia Tbk. Jakarta during the period 2002-2009. The data used is data Working Capital and Rentability At PT. Ades Waters Indonesia Tbk. Jakarta during the period 2002-2009. Working capital significantly influence Rentability On PT Ades Waters Indonesia Tbk. Jakarta during the period 2002-2009. Great influence of the Working Capital in percent against Rentability at PT. Ades Waters Indonesia Tbk. Jakarta during the period 2002-2009 was 38.4%